Microfoundations of Strategic Agility in Emerging Markets: Empirical Evidence of Italian MNEs in India - Ferraris Alberto; Degbey William Y.; Singh Sanjay Kumar; Bresciani Stefano; Castellano Sylvaine; Fiano Fabio; Couturier Jerome (Elsevier, 2022)
We propose the individual-level microfoundations of subsidiary CEOs in emerging markets as antecedents of the strategic agility of multinational enterprises, and subsidiary embeddedness as a key organizational-level moderator of these relationships. Combining quantitative data on subsidiary CEOs operating in India with qualitative interviews with Italian HQ counterparts, our results suggest that subsidiary CEOs’ tenure in emerging markets, along with their overall experience, affects MNE strategic agility positively. Similarly, CEOs’ cognitive characteristics - problem solving and reasoning, and language and communication skills (individual-level microfoundations) - affected strategic agility positively, while subsidiary embeddedness moderated these relationships in different ways, leaving space for fresh managerial and theoretical considerations.